IRRITATED BOWEL SYNDROME IN CHILDREN - V. F. Privorotskiy; N. E. Luppova ("Paediatrician" Publishers LLC, 2012)
Irritated bowel syndrome is a significant and underestimated problem in childhood. This condition is not so good studied in pediatrics in comparison with adult practice. Pediatricians often diagnosed this disease in infants and young children without proper reasons. The authors analyze current opinions about etiology and pathogenesis, clinical presentation, diagnosticsand treatment of irritated bowel syndrome in children. An emphasis is made on diagnostic criteria, which allow suggesting and confirming the diagnosis.